Evaluation of the preference of mice on food intake - Preliminary study - PARONIS (Ε. ΠΑΡΩΝΗΣ), E.; ALEXAKOS (Π. ΑΛΕΞΑΚΟΣ), P.; DIMITRIOU (Κ. ΔΗΜΗΤΡΙΟΥ), C.; BALAFAS (Ε. ΜΠΑΛΑΦΑΣ), E.; KOSTOMITSOPOULOS (Ν. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ), N. (Journal of the Hellenic Veterinary Medical Society, 2017)
One of the possible ways to improve the housing conditions of laboratory animals is to give animals opportunities to perform more species-specific behavioural repertoires through providing enrichment of their environment. Environmental enrichment is, by definition, any modification in the environment of the captive animals that seeks to enhance their physical and physiological well being by providing stimuli meeting the animals' species-specific needs. Food intake is of high concern as this should be promoting the expression of physical feeding behaviour and improves the welfare of the captive animals. The aim of the present study was to evaluate the preference of mice to receive their food from a feeding cup located inside the cage or from the classical food hopper located on the stainless steel wire lid of the cage. Twenty four male C57BL/6 mice, at the age of 5-7 weeks, originated from the breeding colony of the animal facility of the Foundation, were randomly divided into two groups. In group A (n=12) the food was supplied through the food hopper. In group Β (n=12) food was supplied through the feeding cup located in the front side of the cage, as well as through the classical food hopper on the wire lid of the cage. A statistically significant preference of the mice to use the feeding cup instead of the food hopper was noticed (p<0.05). A preference of animals to empty the feeding cup from the food pellets, eat them directly from the bedding and use the feeding cup as a shelter was also observed in all the cages of group B. Based on the above preliminary observations it is concluded that the placement of a feeding cup within the cage could improve the welfare of the animals housed in individual ventilated cages and trigger the expression of a more species-specific feeding behaviour.